Antecedents of Independent Directors on Joint Venture Boards - Olie, René; Klijn, Elko; Reuer, Jeffrey J. (Organization Science, 2024)
The presence of independent directors on corporate boards is often seen as an important means of monitoring to address principal-agent problems and of providing external resources and advice to management. In joint ventures (JVs), however, shareholder-management frictions can be lessened by appointing insiders to management and board positions, whereas access to valuable expertise, resources, and networks are provided by the partners themselves. A natural question, then, is why and when do partners appoint independent directors to JV boards? We argue that the appointment of independent directors to joint venture boards is primarily driven by principal-principal conflict considerations, which are unique in the joint venture context compared with conventional widely held corporations. Consistent with this argument, we find that the likelihood of appointing independent directors increases when JVs face more exchange hazards due to the competitive overlap between partners and the broader functional scope of the JV. However, given that JVs also have alternative governance mechanisms to mitigate shareholder conflicts, we also find that more complex contractual agreements can potentially substitute for independent directors on JV boards. Although relational governance is often highlighted as a key facet of JV governance, we do not find such a substitution effect for this supporting governance mechanism. Overall, our research therefore highlights several interesting domain translation issues when applying existing corporate governance insights to the joint venture setting. Our paper concludes with a call for future research on independent directors serving on JV boards, as JVs represent an organizational form that has been neglected in corporate governance research.